Nanometrology: particle sizing and influence on the toxicological profile - Mota, Wanessa S.; Severino, Patricia; Kadian, Varsha; Rao, Rekha; Zielińska, Aleksandra; Silva, Amélia M.; Mahant, Sheefali; Souto, Eliana B. (Frontiers in Nanotechnology, 2025)
The in vitro and in vivo performance of nanoparticles is directly linked to their physicochemical attributes, i.e., their shape, size, crystal phase and surface properties. By definition, nanoparticles are particles with three external dimensions in the range of 1–100 nm, per ISO 80004-1:2023. They may be naturally occurring, incidental, or intentionally engineered, with their physicochemical properties influencing their biological interactions. Broadly, they have been classified as ultrafine nanoparticles if not intentionally produced, and as engineered nanoparticles produced in a systematic and controlled manner. The designation of “nano,” as affixed to particulate systems, is determined by the size of discrete particles. Therefore, rigorous analysis of particle size and accurate assessment of their properties with a special focus on their particle size distribution, morphology and surface chemistry, is of great importance for their interaction with the biological surroundings. In this review, we discuss the main analytical techniques used in particle size measurements and relate the outcomes with the cytotoxicity and genotoxic profile of nanoparticles commonly used for drug delivery.